THE HEAT TRANSFER FLOW ANALYSIS OF STANDARD PLATE STELL OF JIS G3106 GRADE SM20B ON PRE-HEATING JOINT WEB PLATE I-GIRDER PROCESS CASE STUDY IN PT. BUKAKA TEKNIK UTAMA, BOGOR REGENCY, WEST JAVA PROVINCE - Puspawan, Angky; Pangestu, Mirza Aditya; Suandi, Agus; Alqaf, A. Sofwan Furqon (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2020)
PT. Bukaka Teknik Utama in working on government projects, namely the construction of the Jakarta-Cikampek elevated toll road, the focus of fabrication of steel plates. The steel plate fabrication process, there is a pre-heating process for two steel plates connected by SAW welding with the Joint Web Plate process. During the pre-heating process, conduction heat transfer takes place from the PWHT ceramic to the steel plate. To complete the calculation of the unstable conduction heat transfer two equations are used, namely the equation q transient conduction and q the capacity of the object. Both equations are substituted to get the value of time needed to heat a steel plate from 40oC to 99oC. After calculation and analysis, it can be concluded that the heating time of JIS G3106 Grade SM520B steel plate is directly proportional to the desired temperature. Where the higher the heating temperature is desired, the longer the heating time required to reach the heating temperature. The calculation results obtained the smallest heating time value is 28.695193 seconds at a temperature of 40oC and the largest heating time value is 790.858579 seconds at a temperature of 99oC.